PERANAN POLITIK LEGISLATOR PEREMPUAN DARI KALANGAN SELEBRITAS DI DPR RI 2009-2014 DALAM FUNGSI LEGISLASI - Fadhilah Nur Endah; Nur Hidayat Sardini; Fitriyah . (Journal of Politic and Government Studies, 2016)
ABSTRACTWomen in Indonesia have various occupation backgroundsas means tofulfill their rights as human being. In this day and age, entering politics is nolonger strange for women. Politics is also free to be entered by anyone with anybackground, including celebrity. Women celebrities who participated in politicsare the object of this research. This research aims to discover the political role ofcelebrity legislator in regards to legislative function of DPR RI in 2009-2014 term.To achieve its objectives, this research uses celebrity political theory and thetheory of women's participation in public policy making. This research wasconducted using qualitative method and havedescriptive nature. The subjects werefemale celebrity legislator of DPR RI within 2009-2014 term, namely:OkkyAsokawaty, Venna Melinda, Rachel Maryam.The results of this research shows that women celebrity legislators played anactive role in the parliament’s legislative function and benefited by collegialcollective system in order to run three functions of DPR. However, the researchfinds that women celebrity legislator have not been able to perform legislativefunction in terms of personal proposal for act enactment, less strategic position inparliament for women legislators and also negative stigma of society towardswomen celebrities legislator which could potentially hamper their works.Keywords: Women Legislators, Women Celebrity, Legislative Function